(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This thesis explores the importance of developing pronunciation skills in kindergarten learners and presents a range of activities that can be used to enhance their phonetics, phonology, and oral communication abilities. Through a comprehensive review of literature, the study highlights the significance of early pronunciation development in promoting academic and social success. The research outlines various strategies and techniques that can be utilized by teachers to effectively improve learners’ pronunciation, including phonemic awareness exercises, tongue twisters, songs, chants, and storytelling. The findings of this study provide valuable insights into the effective use of activities for improving pronunciation skills in kindergarten learners, which can aid educators in designing effective curricula and teaching practices that promote successful language acquisition.